Avaliação da reologia no estado fresco de argamassas com substituição de cimento portland por cinza volante, sílica da casca do arroz e metacaulim - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The rheological properties in the fresh state of mortars are associated with the appearance of pathologies. In addition, different ways of allying sustainability with productivity have been search every day in the enterprises, but this requires studies that improve the properties of the mortars in both the hardened state and the rheological behavior in the fresh state. In this way, mineral additions like husk rice silica, fly ash and metakaolin were used to improve the efficiency and productivity of coating mortars, as decreasing the consumption of cement and using materials previously discarded by society, to reduce emissions of carbon dioxide. For the accomplishment of this work, a coating mortar of 8 MPa of compressive stress was used as reference. The best results in fresh rheology of mortars were obtained for cement replacements for 5% of husk rice silica, 5% of husk rice silica with 15% of fly ash or 10% metakaolin.
Keywords: Engenharia civil; Reologia; Cinza de casca de arroz; Squeeze flow; Civil engineering; Rheology; CNPQ::ENGENHARIAS